Significant contribution of subseafloor microparticles to the global manganese budget - Go-Ichiro Uramoto (Nature Portfolio, 2019)
Ferromanganese minerals are abundant in marine environments but the extent of these minerals in subseafloor sediments remains unknown. Here the authors find abundant ferromanganese microparticles in oxic pelagic clays, accounting for 14–16% of the new estimate of the global manganese budget (9.2–47.4 Tt).